2016
DOI: 10.1089/zeb.2015.1187
|View full text |Cite
|
Sign up to set email alerts
|

Karyoevolution inPotamorhina(Cope, 1878) (Ostariophysi, Curimatidae): Using Repetitive DNA for the Elucidation of Genome Organization

Abstract: Some families of Characiformes present the tendency toward stability of the karyotypic macrostructure as Curimatidae, which contains species with a 2n = 54 karyotype and metacentric and submetacentric chromosomes, however, some Potamorhina species contradict to this tendency. Some species of the central Amazon exhibit different diploid number and show intraspecific variation in the location of heterochromatin. By performing cytogenetic characterization by localization of heterochromatin and the nucleolus organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 65 publications
1
14
0
Order By: Relevance
“…The extreme variability in chromosome number and structure (2 n = 54 to 2 n = 102) along with other cytogenetic markers have been the central basis for Feldberg et al’s hypothesis of multiple centric fissions in chromosomes during the evolution of Potamorhina (Figure 1) (Ferdberg et al, 1993). At that time, these cytogenetic findings were placed in the phylogenetic context following the available morphological hypothesis (Vari, 1984), which led them to hypothesize multiple chromosome fissions in the ancestor of P. altamazonica , P. squamoralevis, and P. latior with a subsequent reversion (i.e., chromosome fusions) in P. latior (Pinheiro et al, 2016). However, the recent molecular phylogeny (Melo, Sidlauskas, et al, 2018) and the interspecific relationships presented here (Figure 3) allow us to propose an alternative hypothesis for the chromosome evolution in Potamorhina , which is much simpler than previously thought.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extreme variability in chromosome number and structure (2 n = 54 to 2 n = 102) along with other cytogenetic markers have been the central basis for Feldberg et al’s hypothesis of multiple centric fissions in chromosomes during the evolution of Potamorhina (Figure 1) (Ferdberg et al, 1993). At that time, these cytogenetic findings were placed in the phylogenetic context following the available morphological hypothesis (Vari, 1984), which led them to hypothesize multiple chromosome fissions in the ancestor of P. altamazonica , P. squamoralevis, and P. latior with a subsequent reversion (i.e., chromosome fusions) in P. latior (Pinheiro et al, 2016). However, the recent molecular phylogeny (Melo, Sidlauskas, et al, 2018) and the interspecific relationships presented here (Figure 3) allow us to propose an alternative hypothesis for the chromosome evolution in Potamorhina , which is much simpler than previously thought.…”
Section: Discussionmentioning
confidence: 99%
“…For example, diploid numbers range from 2 n = 54 in P. pristigaster to 2 n = 102 in P. squamoralevis (Feldberg et al, 21993). These extreme variations led authors to hypothesize multiple events of chromosome rearrangements including occurrences of centric fissions and subsequent fusions (reversions) during the evolution of Potamorhina (Figure 1) (Feldberg et al, 1993; Pinheiro et al, 2016). However, this hypothesis was never tested based on molecular phylogenetic approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Rex elements are non-LTR retrotransposons ( Wicker et al , 2007 ) that are extensively distributed through fish genomes ( Ozouf-Costaz et al , 2004 ; Ferreira et al , 2010 ; Borba et al , 2013 ; Schneider et al , 2013 ; Yano et al , 2014 ; Sene et al , 2015 ; Pinheiro et al. , 2016 ), in addition to those of other species.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the distribution of Rex1 and Rex3 in the sex chromosomes, no hybridization sites were identified in the Z and W sex chromosomes of Characidium , whereas these elements are involved in sex chromosome evolution in other species. In particular, Rex3 was detected in the Y chromosome of Chionodraco hamatus ( Ozouf-Costaz et al , 2004 ) and X chromosome of Eigenmannia ( Sene et al , 2015 ); Rex1 and Rex3 were found in the W chromosome of Leporinus ( Borba et al. , 2013 ); and Rex1 , Rex3 , and Rex6 were identified in the Z and W chromosomes of Triportheus ( Yano et al , 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…This gene has been mapped in the chromosomes of several Amazonian fish species, displaying a strong association with heterochromatic regions [Pinheiro et al, 2016]. It has also been proposed that the repetitive DNA organization of the telomeric regions may favor the accumulation of other repetitive sequences, such as transposable elements and satellite DNAs [Arnason et al, 1988;GarridoRamos et al, 1998;Azzalin et al, 2001;Nergadze et al, 2007].…”
Section: Discussionmentioning
confidence: 99%